De-acidification of crude oil using supported ionic liquids phases - Shah, S.N. (Elsevier B.V., 2018)
In this study, imidazolium based ionic liquids with different functional group were chemically tethered to silica support and resulted in silica supported solid ionic liquids phases (SILPs). The SILPS were characterized using CHNS elemental analysis, Fourier Transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and thermo gravimetric analysis (TGA). The adsorption of commercial naphthenic acid from dodecane/kerosene was performed using SILPs. It was observed that their adsorption efficiency varied depending on the functional group on the imidazolium cation. This study was also modeled using COSMO-RS. The SILPs are efficient adsorbent in the extraction of naphthenic acid from highly acidic model oil. The recovery of adsorbed naphthenic acids from the SILPs was also investigated. Â© 2017 Elsevier B.V.